TRAINING ON THE UTILIZATION OF QUIZZ MEDIA AS A LEARNING EVALUATION MEDIA AT SDN TAMBAKAGUNG MOJOKERTO - Dayu, Dian Permatasari Kusuma; Cindy, Agustin; Aprilia, Septi; Nurainiyah, Nurainiyah (Abdi Masya, 2025)
The problem in this study is the limited understanding and skills of teachers at SDN Tambakagung Mojokerto in utilizing technology for learning evaluation. Many teachers are not yet accustomed to using digital platforms such as Quizizz to compile interactive and efficient evaluation questions. This causes the evaluation process to tend to be conventional, monotonous, and takes a long time to analyze the results. In addition, some teachers do not yet know the full potential of Quizizz features that can help increase student engagement in learning. This activity is in the form of training, direct practice, and mentoring for teachers in using Quizizz. The community service aims to provide training to teachers at SDN Tambakagung Mojokerto on the use of Quizizz as a learning evaluation medium. Quizizz, as a technology-based learning platform, can increase the effectiveness of evaluation by providing interactive questions and fast analysis of results. This training includes an introduction to Quizizz features, quizzes, and implementation in the learning evaluation process. Training on the use of Quizizz as a learning evaluation medium at SDN Tambakagung Mojokerto has had a positive impact on improving teacher skills in utilizing technology for learning evaluation. Through training tailored to the needs and level of understanding of teachers, participants successfully mastered the use of the Quizizz platform to create interactive quizzes that can increase student engagement at SDN Tambakagung Mojokerto.